Analisis Pengaruh Kualitas Produk dan Lokasi terhadap Kepuasan Konsumen Kopi SOE di Kalangan Gen Z Jakarta Barat - Yogi Permana (INVESTASI : Inovasi Jurnal Ekonomi dan Akuntansi, 2025)
This research highlights the importance of marketing in achieving company targets by meeting consumer preferences and expectations. Coffee shops in West Jakarta offer high-quality coffee and a comfortable atmosphere, which are key factors for business success. PT EOS Maju Bersama, through the Kopi Soe brand, has been innovating since 2018 and has more than 200 franchise outlets. This study aims to determine the influence of product quality and location on the purchase satisfaction of Kopi Soe among Gen Z in West Jakarta. The research uses a quantitative descriptive method with surveys. A pre-survey was conducted with 25 respondents to examine various issues related to the research, while the sample related to the title consisted of 96 respondents. The sample was determined using the Non Probability Sampling method and the Purposive Sampling technique. The results showed that both partially and simultaneously, product quality and location have a positive and significant impact on purchase satisfaction, with the regression equation Y = 0.373 + 0.439X1 + 0.587X2. The partial determination coefficient value is 0.824 with a percentage of 82.4% for the product quality variable and 0.813 with a percentage of 81.3% for the location variable. The simultaneous determination coefficient value is 0.866 with a percentage of 86.6%.